2020
DOI: 10.1177/1535370220931509
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length in different metabolic categories: Clinical associations and modification potential

Abstract: Cardio-metabolic disorders, including type 2 diabetes, are known to be associated with accelerated attrition of telomeres, recognized as genetic and biological markers of aging. Some common genetic characteristics were found regarding the presence of shorter telomeres and the development of type 2 diabetes. However, there are conflicting epidemiological reports regarding the association of leukocyte telomeres lengths with type 2 diabetes: not only the causality of such a link remains unclear, but not all resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 66 publications
(97 reference statements)
0
8
0
1
Order By: Relevance
“…An association of short LTL with higher risk for developing type 2 diabetes has been also demonstrated; this association, however, was significantly influenced by body mass index (BMI), diabetes type, age, region, and sex (Zhao et al, 2013 ; Willeit et al, 2014 ; Wang et al, 2016 ; Krasnienkov et al, 2018 ). Short LTL was also shown to be associated with different aspects of metabolic syndrome (Khalangot et al, 2017 , 2019 , 2020 ). Accelerated telomere shortening and low telomerase activity were shown to be associated with skeletal pathologies mediated by the age-related abnormal reconstruction of the subchondral bone, such as osteoporosis and osteoarthritis (Fragkiadaki et al, 2020 ).…”
Section: Tl and Diseasementioning
confidence: 99%
“…An association of short LTL with higher risk for developing type 2 diabetes has been also demonstrated; this association, however, was significantly influenced by body mass index (BMI), diabetes type, age, region, and sex (Zhao et al, 2013 ; Willeit et al, 2014 ; Wang et al, 2016 ; Krasnienkov et al, 2018 ). Short LTL was also shown to be associated with different aspects of metabolic syndrome (Khalangot et al, 2017 , 2019 , 2020 ). Accelerated telomere shortening and low telomerase activity were shown to be associated with skeletal pathologies mediated by the age-related abnormal reconstruction of the subchondral bone, such as osteoporosis and osteoarthritis (Fragkiadaki et al, 2020 ).…”
Section: Tl and Diseasementioning
confidence: 99%
“…Previous studies have reported hypoadiponectinemia to act as a biomarker for insulin resistance and an independent risk factor for cardiovascular diseases and T2DM [ 52 ]. Other determinants that have been linked to an increased rate of TL shortening as well as increased cardiovascular risk include obesity, hypertension, deranged fasting plasma glucose, and high triglyceride with or without low HDL levels [ 53 ]. Our data align with a recent study undertaken in a multiethnic Asian population, which reported ethnic variation in the association between obesity indices (BMI and visceral fat area) and short TL in T2DM patients [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Жінки, що перенесли втрати вагітності, зазнають стресу, через що порушуються функції цілого організму [7,9,15,16]. Вони також мають підвищений ризик кардіоваскулярних захворювань [14], які, як відомо, асоціюються із короткими теломерами [4,6]. Отже, довжина теломер є суттєво меншою у жінок із ранніми репродуктивними втратами.…”
Section: результати та обговоренняunclassified